Avaliação de desempenho de modelos para estimativas de evapotranspiração de referência para região de Palotina, Paraná - Syperreck, Vera Lucia Greco (2006)
The aim of this study was to compare the efficiency of three estimate methods for reference evapotranspiration with the FAO Penman-Monteith equation. Meteorological data used in this study were collected from the IAPAR meteorological station, located in Palotina, Paraná State. In order to estimate the reference evapotranspiration, the data available from 1994 to 2003 were collected. The performance of the Thornthwaite, Camargo and Hargreaves-Samani methods were compared to the FAO Penman-Monteith equation. The average of daily reference evapotranspiration ranged from 2.18 e 3.62 mm.day-1. The results indicated that the evaluated methods showed a good adjustment when compared to the FAO Penman-Monteith method, according to the daily scale. The correlation coefficient (r) ranged from 0.78 to 0.80. The coefficient of accuracy or agreement (d) presented values that ranged from 0.65 to 0.73. In comparison to the FAO Penman-Monteith method, the Hargreaves-Samani method demonstrated slight performance while the Thornthwaite and Camargo presented poor performance, evaluated by the index (c)